FRI0591 Whole-body mri demonstrates reduction of inflammation in peripheral joints and entheses during tnf-inhibitor treatment in patients with axial spondyloarthritis, but also age-dependent persistent inflammation in joints prone to osteoarthritis. (12th June 2018) - Krabbe, S.; Østergaard, M.; Eshed, I.; Sørensen, I.J.; Møller, J.; Jensen, B.; Madsen, O.R.; Klarlund, M.; Pedersen, S.J.
Abstract : Background: Patients with predominantly axial spondyloarthritis (axSpA) may also have inflammation of peripheral joints and entheses. Using a whole-body MRI (WBMRI) approach, peripheral joints and entheses can be assessed objectively and followed during treatment. Objectives: To describe the localization and extent of inflammation of peripheral joints and entheses by WBMRI in patients with axSpA initiating TNF-inhibitor therapy, and to assess treatment-induced changes. Methods: Fifty-three patients that fulfilled the ASAS criteria for axSpA were included. MRI of SIJs and spine and WBMRI of peripheral joints and entheses were performed at baseline and 4/16/52 weeks after starting TNF inhibitor treatment. 75 peripheral joints and 30 peripheral entheses were scored in chronological order by an experienced musculoskeletal radiologist (IE). Osteitis, synovitis and entheseal soft tissue inflammation were scored separately [0(none)/1(mild)/2(moderate/severe)]. A WBMRI peripheral joint and enthesis index (WBMRI index) was derived by summing scores of all peripheral lesions. Results: Median age (IQR/range) was 35 years. (28–44/22–73); median symptom duration was 5 years. (3–13/0–31); 53% were male. Baseline median WBMRI index (n=53) was 7, 4–14; 0–40 after 52 weeks (n=46) 4 (2–9; 0–26). WBMRI index decreased mean 0.6 at week 4 (p=0.17, paired t-test), 2.3 at week 16 (p<0.001) and 3.2 at week 52 (p<0.001). Thirty-seven patients (70%) had a relatively low baseline WBMRI index (≤10) with minor change over time, while patients with higher baseline scores tended to change more (figure 1A). The most frequently involved sites (≥15% of patients) were typical for SpA (sternoclavicular joint/plantar fascia) or osteoarthritis (carpometacarpal-1/metatarsophalangeal-1 synovitis). In univariate analysis, WBMRI index at week 52 was associated with age (2.5 higher per 10 years increase in age, p<0.001) and male sex (3.6 lower in men, p=0.021), but not with body-mass index, HLA-B27, C-reactive protein or ASDAS at week 52. In multivariate regression with age and sex as covariates, only age was significantly associated with WBMRI index (2.3 per 10 years increase in age, p<0.001) whereas sex was not (p=0.24). In univariate analysis, higher age was not significantly associated with change in WBMRI index, but when adjusted for baseline WBMRI index, higher age was associated with a less prominent reduction in WBMRI index (+0.9 per 10 years increase in age). Conclusions: Inflammation of peripheral joints and entheses decreased over time in a cohort of patients with predominantly axSpA. Most patients had WBMRI index above zero during follow-up, and this was related to age and involved sites prone to osteoarthritis. Thus, the WBMRI Index may capture both disease activity related to axSpA and age-related degenerative changes. Disclosure of Interest: None declared